Pentingnya Sertifikasi Halal dalam Meningkatkan Daya Saing Produk Didesa Kota Guring - Aqila Fadhil; Kanada Komariyah; Clhora Meiroati; Luthfi Aji Santoso; Merry Amelia; Sena Tarisma; Sepri Minarto; Wanda Novita (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
Halal certification plays a crucial role in enhancing product competitiveness, particularly in Kota Guring Village. Many producers in this village do not fully understand the benefits of halal certification, which may reduce their products' competitiveness in both local and international markets. This study aims to analyze the importance of halal certification in increasing product competitiveness in the village. The method used includes surveys and interviews with local producers as well as secondary data analysis from various related sources. The results show that halal certification can increase consumer trust, expand markets, and improve product quality. Therefore, halal certification is an important strategy that local producers need to adopt to compete in broader markets.